Identification of Translation Strategies Application by Tourism Practitioner for Cultural-Specific Item - Kadek Wiramarta; Ni Putu Dian Utami Dewi; Ida Bagus Wika Krishna; Krisna Sukma Yogiswari (Universitas Pendidikan Indonesia, 2022)
Bali relies on culture as one of its tourism attractions. Therefore, tourism practitioners are demanded to have strategies in translating cultural-specific items. On the other side, although the topic of translation has received considerable amount of interest, strategies of tourism practitioner in translating cultural-specific items is rarely researched. Therefore, this research focuses on strategies executed by tourism practitioners in cultural language translation as well as the aspects that influence the selection of translation strategies. This research involves 74 respondents of tourism practitioners in Bali Indonesia who are asked to translate 28 cultural-specific items in context. The collected data are analyzed by using Baker theories of translation (1992). From the analysis, it is found that loanword or loanword with explanation was used dominantly with 57.77%. The second dominant translation strategy was paraphrasing by using unrelated words with 22.78%. The third dominant translation strategy was using a more general word with 8.49%. Next dominant translation strategy was cultural substitution with 6.61%. The fifth dominant translation strategy was paraphrasing by using related word with 2.41%. Finally, the least dominant translation strategy was negligence or omission with 1.16%. In terms of reasons, communicativeness, guest cognition, cultural awareness, cultural complexity and guest’s personality are found to be the ones which influence the selection of translation strategies.